The High Immunity Induced by the Virus-Like Particles of Foot-and-Mouth Disease Virus Serotype O - Xiao, Yan; Zhang, Suling; Yan, He; Geng, Xiaolin; Wang, Yanwei; Xu, Xin; Wang, Mengyue; Zhang, Haohao; Huang, Baicheng; Pang, Wenqiang; Yang, Ming; Tian, Kegong (Frontiers in Veterinary Science, 2021)
Foot-and-mouth disease (FMD), caused by food-and-mouth disease virus (FMDV), is a highly contagious and economically devastating viral disease of cloven-hoofed animals worldwide. In this study, the co-expression of Small Ubiquitin-like Modifier (SUMO)-fused capsid proteins of FMDV serotype O by single plasmid in Escherichia coli (E. coli) was achieved with an optimal tandem permutation (VP0-VP3-VP1), showing a protein yield close to 1:1:1. After SUMO removal at a low level of protease activity (5 units), the assembled FMDV virus-like particles (VLPs) could exposure multiple epitopes and have a size similar to the naive FMDV. Immunization of pigs with the FMDV VLPs could induce FMDV-specific humoral and cellular immune responses effectively, in a dose-dependent manner. These data suggested that the stable FMDV VLPs with multiple epitopes exposure was effective for the induction of an immune response in pigs, which laid a foundation for the further development of the FMDV subunit vaccine.